Surgical management of obstructive right-sided colon cancer at a national level results of a multicenter study of the French Surgical Association in 776 patients. Issue 10 (October 2018) - Mege, Diane; Manceau, Gilles; Beyer-Berjot, Laura; Bridoux, Valérie; Lakkis, Zaher; Venara, Aurélien; Voron, Thibault; Brunetti, Francesco; Sielezneff, Igor; Karoui, Mehdi
Abstract: Aim: To report the results of surgery for obstructive right colon cancer (ORCC) and to identify risk factors associated with worse outcomes that may help surgeons to choose the best surgical option. Methods: This is a retrospective national cohort study, including all patients operated on for ORCC from 2000 to 2015. Those treated with colonic stent or symptomatic treatment were excluded. We described outcomes after surgery for ORCC and performed multivariate analyses for mortality, morbidity and survival. Results: Among 776 patients analyzed, 716 (92%) had their primary tumor removed, with primary anastomosis in 582 (82%). The remaining 194 underwent anastomosis with loop ileostomy (n = 21), resection with double-end stoma (n = 113), defunctioning stoma without resection (n = 48) and ileocolic by-pass (n = 12). Postoperative mortality, morbidity and anastomotic leak rates were 10%, 51% and 14%, respectively. In multivariate analysis, age >70, ASA score ≥3 and hemodynamic instability were predictors of postoperative mortality whereas ASA score ≥3, hemodynamic instability and intra-operative complications were predictors of severe morbidity. No factors were correlated with anastomotic leak. After a median follow-up of 26 months, 8% of patients were alive with a permanent stoma. Five-year overall, disease-free and cancer-specific survival was 42%, 42% and 62%, respectively. In multivariate analysis, peritonitis, synchronous metastases and absence of adjuvant chemotherapy were predictors of decreased overall survival. Conclusions: Emergency surgery for ORCC is associated with high mortality and morbidity. Two third of patients with ORCC can be managed with resection and primary anastomosis. For high-risk patients, a staged surgical management may be discussed.